Nutritional status, Vitamin D and glucose metabolism: relatives or colleagues? - Mennini, Maurizio; Pallotti, Francesco (Progress in Nutrition, 2014)
Dear Editor,the general recommendation that breastfed infants requirevitamin D (VitD) supplementations is widely accepted and many studies stress the need to start supplementation of 400 UI/d from birth (1), in order to maintain bone health in children as well in adults.[...]